Serosurvey and Cellular Immune Status of HTLV-1/2 and HIV Co-infections in Bauchi State, Nigeria - Babayo, Adamu; Azeez, Akande Oyebanji; Sabo, Yusuf Mohammed; Abdullahi, Idris Nasir; Dangana, Amos (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Human T-cell lymphotropic virus types 1 and 2 (HTLV-1 & 2) are frequent co-pathogens among immunosuppressed individuals, particularly HIV/AIDS infected persons. Dual infected persons usually present with false normal or high CD4+ T cells count as a result of the ability of HTLV to induce clonal proliferation of CD4+ T lymphocytes. There is paucity of information on this clinical entity in Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. This study aimed to determine the seroprevalence of HTLV-1/2 and associated cellular immune response among antiretroviral naïve and experienced HIV infected persons at Bauchi State, Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. One hundred and eighty two (182) HIV seropositive patients’ blood samples were analyzed for anti HTLV-1/2 IgM and IgG antibodies using ELISA while CD4+ T cells were counted using Flow cytometry technique. Socio-demographic data of the subjects and clinical history were obtained via questionnaire and medical records, respectively. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The seroprevalence of anti-HTLV-1/2 was 14%. This comprised 76 (41.8%) males and 106 (58.2%) females. Six (3%) were seropositive for both ant-HTLV -1&2 IgM and IgG. Of the total positive for anti-HTLV-1/2, 20 (25%) ART-naïve and 6(5.9%) ART-experience subjects. Whole blood CD4+ T cell count was significantly high in HTLV-1/-2 IgG/IgM seropositive subjects compared to their HTLV-1/-2 negative counterpart. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. All subjects (100%) who were HTLV-1/-2/HIV co-infected had normal to higher CD4+ T cell counts. It is suggested to be very careful in using only CD4+ counts to monitor HIV progression or as indicators for ART.